2018
DOI: 10.1111/jgh.14065
|View full text |Cite
|
Sign up to set email alerts
|

Combination of increased visceral fat and long segment involvement: Development and validation of an updated imaging marker for differentiating Crohn's disease from intestinal tuberculosis

Abstract: Necrotic lymph nodes are exclusive for ITB, and the combination of long segment involvement and VF/SC ratio > 0.63 is exclusive for CD, and these features can make a definite diagnosis in 43% patients with a CD/ITB dilemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This was validated in a separate validation cohort, with similar diagnostic accuracy. We further combined the CT features and VF/SC ratio to develop an updated model and showed that necrotic lymph nodes, long segment involvement, and VF/SC ratio > 0.63 were most significantly different between CD and ITB, both in the development and validation cohort[61]. Like the previous meta-analysis, presence of necrotic lymph node was exclusive for ITB, and so was not included in the model.…”
Section: Radiologymentioning
confidence: 99%
“…This was validated in a separate validation cohort, with similar diagnostic accuracy. We further combined the CT features and VF/SC ratio to develop an updated model and showed that necrotic lymph nodes, long segment involvement, and VF/SC ratio > 0.63 were most significantly different between CD and ITB, both in the development and validation cohort[61]. Like the previous meta-analysis, presence of necrotic lymph node was exclusive for ITB, and so was not included in the model.…”
Section: Radiologymentioning
confidence: 99%
“…For imaging characteristics, especially CTE/MRE, patients with CD were more likely to show comb sign, target sign, adipose creeping sign and ≥4 segments involved. Kedia et al showed that comb sign was more common in CD [17], and no studies had compared target sign or adipose creeping sign in ITB and CD, but some studies have used them to build the differential models [8,18]. In our study, these three factors were probably easy to get influenced by other factors, and they failed to be selected as potential parameters in CART.…”
Section: Discussionmentioning
confidence: 77%
“…The models integrating clinical, endoscopy, pathology, and CTE are summarized in Table 2. 18,[24][25][26]28…”
Section: Models Integrating Clinical Endoscopy Pathology and Ctementioning
confidence: 99%
“…All models were reported to have an AUROC value greater than 0.85. However, only the models by Makharia et al, 6 Jung et al, 17 Mao et al, 18 Kedia et al, 28 Bae et al, 35 Wu et al, 36 He et al, 37 and Limsrivilai et al 38 were tested in validation cohorts in their original studies. Among those models, the models by Makharia et al, 6 Mao et al, 18 Bae et al, 35 Wu et al, 36 and He et al 37 were developed and validated based on prospective data.…”
Section: Model With Adjustable Integrated Variablesmentioning
confidence: 99%